(untitled) - Petroutsos, Evangelos (San Francisco, 1998)
Mastering Visual Basic 6 is the ideal guide to Visual Basic. Inside, you'll master the environment, the features, and the techniques that are key to professional Windows programming. Clear, in-depth instructions from a Visual Basic expert provide essential knowledge through scores of practical examples. For beginning, intermediate, and advanced Windows programmers; in-depth coverage of ActiveX programming and code optimization.
Keywords: BASIC (Ngôn ngữ lập trình máy tính),BASIC (Computer program language)